2014
DOI: 10.1590/1982-021620145313
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização do desenvolvimento da alimentação de crianças nascidas pré-termo entre três e 12 meses

Abstract: Objetivo caracterizar o desenvolvimento da alimentação de um grupo de prematuros, entre três e 12 meses, nascidos em Canoas/RS, verificando o tipo de aleitamento, época de introdução da alimentação complementar, hábitos orais deletérios, orientações recebidas, dificuldades alimentares e perfil sociodemográfico. Métodos essa pesquisa foi avaliada e aprovada pelo comitê de ética da da ULBRA sob Nº. 2011-480H CEP-ULBRA. Trata-se de um estudo descritivo, quantitativo e transversal. Foi realizada entrevista com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 22 publications
2
15
0
13
Order By: Relevance
“…This result is similar to the one verified by Brusco and Delgado 21 , in which half of the sample formed by preterm infants used pacifiers, and near the result of 45.7% found by Benevenuto de Oliveira et al 17 Primiparity has presented statistical association to the use of pacifier (80.8%) compared to infants who did not use it (38.5%), which was also observed by Buccini, Benício and Venancio 8 . This is probably related to the mother's lack of experience in interpreting her child's needs.…”
Section: Discussionsupporting
confidence: 88%
“…This result is similar to the one verified by Brusco and Delgado 21 , in which half of the sample formed by preterm infants used pacifiers, and near the result of 45.7% found by Benevenuto de Oliveira et al 17 Primiparity has presented statistical association to the use of pacifier (80.8%) compared to infants who did not use it (38.5%), which was also observed by Buccini, Benício and Venancio 8 . This is probably related to the mother's lack of experience in interpreting her child's needs.…”
Section: Discussionsupporting
confidence: 88%
“…Despite this knowledge, breastfeeding rates among preterm newborn are still low 11 . Few studies report the duration of breastfeeding after hospital discharge, throughout the first year of life, among newborn below 33 weeks of gestation [12][13][14][15] . This knowledge is important for the promotion of breastfeeding maintenance strategies in this group of infants.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to gestational age of preterm infants, one study found associations between gestational age at birth (extreme prematurity) and flaccidity of oral structures 30 . Another study found more alterations in the orofacial sensory motor system development in infants with a gestational age less than or equal to 34 weeks, than in infants with gestational age of 35-36 weeks 31 .…”
Section: Resultsmentioning
confidence: 99%